REDUCING IMPRISONMENT RATES AND PREVENTION OF CRIMINALITY IN CONPEMPORARY GEORGIA - Glonti, Aleksandre (European Scientific Journal, ESJ, 2012)
Combating to crime is a challenge for modern-day Georgia since the "Rose Revolution". Over the past 8 years the crime rate has decreased on average three times and also significantly reduced the level of population victimization. At the same time, the number of people serving sentences in prison dramatically increased. According to statistical data in Georgia the number of prisoners per capita is one of the highest in the world which can be considered as a very negative factor for political image of country and requires serious reform of criminal legislation in order to decriminalize the criminal violations that are not grave. The author of the article examines some of the offenses for which legislator should mitigate the sanctions excepting the deprivation of liberty.